Crowding-induced opening of the mechanosensitive Piezo1 channel in silico - Wenjuan Jiang (Nature Portfolio, 2021)
Mechanosensitive Piezo1 channels transduce mechanical stimuli into electrochemical signals. Jiang et al. show that due to the bending rigidity of the membrane, the overlap of neighboring Piezo1 footprints produces a flattening of the Piezo1 footprints and a cation-selective conducting pore. This study suggests that the clustering of Piezo1 channels may tune its sensitivity to applied force.